Chloride Balance in Preterm Infants during the First Week of Life - Silvia Iacobelli; Elsa Kermorvant-Duchemin; Francesco Bonsante; Alexandre Lapillonne; Jean-Bernard Gouyon (Hindawi Limited, 2012)
Objective. To describe the chloride balance in infants born 25-32-week gestation, analyze the association of chloride changes with hydroelectrolytic status and their relationship with perinatal conditions, morbidities, and neurological outcome. Methods. For 7 days after birth, sodium and chloride balance, plasma potassium, phosphate, and total carbon dioxide (tCO2) were prospectively determined and strong ion difference (SID) calculated. Three multivariate regression analyses were performed to identify factors associated with high plasma chloride concentration, low SID, and low tCO2. Results. 107 infants were studied. Plasma chloride concentration was significantly positively associated with plasma sodium concentration. Higher plasma chloride and lower SID were significantly associated with lower plasma tCO2. Chloride intake was the main independent factor associated with high plasma chloride, low SID, and low plasma tCO2, with lesser contribution of sodium intake and low gestational age (GA). Also, patent ductus arteriosus and birth weight loss were independent factors affecting plasma chloride and SID. Neither high chloride levels nor low SID were associated to impaired neurological outcome. Conclusions. In preterm infants, chloride balance is influenced by GA and by interrelationship between sodium and chloride intake. High chloride levels are associated with metabolic acidosis but not related to increased risk of impaired neurological outcome.